DEVELOPMENT AND VALIDATION OF DERIVATIVE SPECTOSCOPIC METHOD FOR SIMULTANEOUS DETERMINATION OF ATORVASTATIN AND RAMIPRIL IN COMBINED DOSAGE FORM - DR. ATUL PATEL,; DR. HITESH JOGIA, (International Journal of Pharma and Bio Sciences, 2013)
A novel, simple, accurate, sensitive, reproducible, the economical spectroscopic method has been developed and validated for the determination of Atorvastatin and Ramipril in combined dosage form. First order derivative spectroscopy method is adopted to eliminate spectral interference. The method obeys Beer’s Law in concentration range of 15-35 µg/ml for Atorvastatin and 7.5-17.5 µg/ml for Ramipril. The method was validated for linearity, range, accuracy, precision and specificity as per ICH guidelines. Zero crossing point for Atorvastatin and Ramipril was 223 nm and 296 nm respectively in methanol. The developed method as successfully used for the quantitative analysis of commercially available dosage form.